(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Cleaning validation is an integral operation of good manufacturing practice in pharmaceutical industry. The aim of this study was to validate simple analytical method for detection of 2-propanol residue in equipment, which is likely contaminated with 2-propanol, usually used in the production area. The gas chromatography with flame ionization detection (GC-FID) method was validated on a GC system using DB-FFAP capillary column at the flow rate of 4.9 mL/min. The calibration curve was linear over concentration range from 2.8µg/mL to 110.7µg/mL with a correlation coefficient equal to 0.99981. The detection limit (LOD) and quantitation limit (LOQ) were 1.1µg/mL and 2.8µg/mL, respectively. The simplicity of gas chromatography method makes it useful for routine analysis of 2-propanol residue and is an alternative to corresponding methods.